Physicochemical Characteristics of Malaysian Stingless Bee Honey from Trigona Species - IJ, Fatima; AB, Mohd Hilmi; I, Salwani; M, Lavaniya (IIUM Medical Journal Malaysia, 2018)
The physicochemical properties of stingless bee honey are diverse according to origin of geographical or botanical and fruit or flower season. These factors result in production of honey with different colour, pH, ash and water content although the bee species is similar. To date, the physicochemical properties of honey from Malaysian Trigona species are unknown. Therefore, determination of physicochemical properties of honey from stingless bee is crucial for Malaysian researchers in order to analyse the purity of the honey. Five honey samples were used for the current study. Four samples were stingless bee honey from two of the most common domesticated Malaysian stingless bee species; Trigona thorasica and Trigona itama. Meanwhile, one sample was from Tualang honey. For stingless bee honey, the values for pH, moisture content, electrical conductivity, ash content and hydroxymethylfurfural (HMF) were 2.79±0.04 to 2.95±0.02, 28.3±0.68 to 33.7±0.51, 0.47±0.22 to 0.55±0.38, 0.132±0.03 to 0.532±0.83 and 0.080±0.16 to 3.42±1.03, respectively. The colour of stingless bee honey varies based on observation or absorbance assay. The study described the physicochemical properties derived from Malaysian bees of Trigona thorasica, Trigona itama, and Apis Dorsata.